2010
DOI: 10.1007/s12519-010-0221-0
|View full text |Cite
|
Sign up to set email alerts
|

Iodine nutritional status and goiter prevalence in 6–12 years primary school children of Saurashtra region, India

Abstract: There is mild goiter prevalence in primary school children of Rajkot district, which is due to the inadequate iodine intake or content from salt at the household level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…Makwan et al, study shows the overall prevalence of goiter among the study population was 4.83%. [7][8][9] Findings contrary to our study were observed in a study conducted by Chandwani et al, where the prevalence was found to be 23.2%. 10 About 97.2% of the salt sample had iodine concentration ≥15 and none had zero iodine content.…”
Section: Resultscontrasting
confidence: 92%
“…Makwan et al, study shows the overall prevalence of goiter among the study population was 4.83%. [7][8][9] Findings contrary to our study were observed in a study conducted by Chandwani et al, where the prevalence was found to be 23.2%. 10 About 97.2% of the salt sample had iodine concentration ≥15 and none had zero iodine content.…”
Section: Resultscontrasting
confidence: 92%
“… 25 Iodine-deficient populations have higher serum TSH concentrations and lower serum T4 concentration, as the pituitary gland secretes TSH in response to circulating levels of T4, and the serum TSH rises when serum T4 concentrations are low. 26 The mean serum T3 was found to be in a high normal level, the mean serum T4 was found to be in a low normal level, and the mean serum TSH was found to be in a high level. 13 This may be explained by thyroidal secretion of T4 and T3 in the proportion in which they exist within the gland, preferential secretion of T3, or increased peripheral conversion of T4 to T3.…”
Section: Discussionmentioning
confidence: 86%
“…Iodine deficiency disorders (IDDs) is the most common cause of preventable brain damage, mental retardation and stunted growth in children. 1 More than 90% of iodine intake is excreted in urine, thus urinary iodine excretion (UIE) is considered a good biochemical marker of recent dietary intake of iodine. 2 Thyroid hormones are essential for growth and development of the brain and central nervous system and the regulation of important metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were observed in a study done by Chudasama RK et al in Saurasthra region showed the prevalence rate of 8.8% and a study by Pushpa Sarkar et al, in neighbouring district Mandya, showed that the prevalence rate was 6.6% in school children and females had a higher prevalence compared to males in all the age groups. 8,9 Makwan NR et al ,study shows the overall prevalence of goiter among the study population was 4.83%. 4 Contrast to our study findings, higher prevalence rate of goiter (13.2%) was observed in a study by Kapil U, 10 Haresh Rameshkumar Chandwani et al study in Bharuch district, Gujarat (23.2%) 11 and Kamath R et al study in Rural Belgaum,16.6%.…”
Section: Discussionmentioning
confidence: 91%